Penelitian Magnetostratigrafi dan Penerapan Satuan Stratigrafi Polaritas Magnet sebagai Satuan Kronostratigrafi: Studi Kasus di Cekungan Bandung serta Daerah Mojokerto dan Sangiran, Jawa - Sunardi, Edi (Indonesian Journal on Geoscience, 2010)
DOI: 10.17014/ijog.v5i2.99Palaeomagnetism has a role to make a new stratigraphic nomenclature based on the earth magnetism of a nonperiodic reversal polarity phenomenon. Since this phenomenon has a global impact, it can be used as a potential correlation, known as the Magnetic Polarity Chronostratigraphy Unit. Remanent magnetism direction having reversal polarity against present earth magnetic field has long been known since early palaeomagnetic studies. Modern development of geomagnetic polarity time scale (GPTS), initiated in early 1960’s has followed the advancement of radiometric dating which is more accurate. A palaeomagnetic record obtained in the past of 3 Ma of rock in the Sangiran Area, East Java, has contributed in making a correction of previous magnetostratigraphy researches as well as a new level stratigraphy boundary and a new event of geomagnetic polarity. Based on the correlation record of secular variation in Mojokerto and Sangiran, the magnetostratigraphy of formations of Pleistocene age at Mojokerto has been arranged. The geomagnetic polarity stratigraphy of the past 4 Ma of the rocks in the Bandung Basin and its surrounding areas can be used as a guidance of isochronous position in the stratigraphy correlation.